KIP-K Scholarship Eligibility for Economically Established Students: Perspectives of Muhammadiyah and Nahdlatul Ulama Figures - Qomariyah, Nurul; Putri, Eka Desiana; Aziz, Muhammad Irfan; Musafa'ah, Suqiyah (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2026)
The Indonesia Smart College Card Scholarship (KIP-K) is an assistance program organized by the government with the aim of easing the burden of education costs for students from underprivileged families. However, in practice, many underprivileged students receive KIP-K scholarships. This study examines in depth the comparative analysis of the views of NU and Muhammadiyah figures regarding the provision of KIP scholarships to underprivileged students. This type of research is a normative-empirical law with a descriptive-comparative approach. Data was obtained through literature studies and in-depth interviews with figures from Muhammadiyah and Nahdlatul Ulama. The data were analyzed comparatively. The results of the study show a difference in approach between Muhammadiyah and Nahdlatul Ulama (NU) figures regarding the ethics of the utilization of scholarship, especially the KIP-K program. Muhammadiyah leaders tend to emphasize a normative, procedural approach grounded in maqāṣid al-syarī'ah, particularly the principles of ḥifẓ al-'aql (safeguarding reason) and ḥifẓ al-māl (safeguarding property). Meanwhile, NU figures highlight aspects of social ethics and pesantren values, such as honesty, trust, and social responsibility. The similarity between the two lies in the understanding that scholarship is a mandate that must be used honestly and on target, and that any deviation is a violation of Islamic law. Both Muhammadiyah and NU leaders view the act of receiving scholarships illegally as a form of deprivation of rights that are not justified by morality and Islamic law.